Beyond H2S and NO interplay: Hydrogen sulfide and nitroprusside react directly to give nitroxyl (HNO). A new pharmacological source of HNO - Filipovic, Milos; Eberhardt, Mirjam; Prokopovic, Vladimir; Mijuskovic, Ana; Orescanin-Dusic, Zorana; Reeh, Peter; Ivanovic-Burmazovic, Ivana (Journal of Medicinal Chemistry, 2013)
Hydrogen sulfide (HS) has been increasingly recognized as an important signaling molecule that regulates both blood pressure and neuronal activity. Attention has been drawn to its interactions with another gasotransmitter, nitric oxide (NO). Here, we provide evidence that the physiological effects observed upon the application of sodium nitroprusside (SNP) and HS can be ascribed to the generation of nitroxyl (HNO), which is a direct product of the reaction between SNP and HS, not a consequence of released NO subsequently reacting with HS. Intracellular HNO formation has been confirmed, and the subsequent release of calcitonin gene-related peptide from a mouse heart has been demonstrated. Unlike with other thiols, SNP reacts with HS in the same way as rhodanese, i.e., the cyanide transforms into a thiocyanate. These findings shed new light on how HS is understood to interact with nitroprusside. Additionally, they offer a new and convenient pharmacological source of HNO for therapeutic purposes. © 2013 American Chemical Society.